Analysis of the Implementation of the ‘Love-Based Curriculum’ in Early Childhood Education: The Role of Teachers and Supporting Learning Materials - Nurul Fitria Kumala Dewi; Rohmah Wati; Sulimah (Fakultas Keguruan dan Ilmu Pendidikan, 2026)
Education is the primary means of instilling moral values, empathy, and compassion from an early age. The Ministry of Religious Affairs of the Republic of Indonesia (MoRA) introduced the Love-Based Curriculum as an effort to develop an educational system that emphasizes the values of humanity, tolerance, and respect for diversity. This study aims to describe the implementation of the Love-Based Curriculum concerning the role of teachers and supporting learning materials at RA An Najwa. This study employed a qualitative approach using a descriptive method. The research participants consisted of the school principal and teachers. Data were collected through observations, interviews, and documentation. The findings indicate that the implementation of the Love-Based Curriculum at RA An Najwa is still in its initial stage and has therefore not yet been implemented optimally. Teachers have made efforts to instill the values of compassion, empathy, and tolerance in learning activities; however, their understanding of the curriculum remains limited due to the lack of socialization and technical guidance provided by the Ministry of Religious Affairs. The learning media and instructional materials currently used are still conventional and have not fully supported the systematic implementation of the values of the Love-Based Curriculum. Therefore, continuous training, technical assistance, and the development of love-based learning media are needed to ensure that the curriculum can be implemented effectively in accordance with the objectives of the Ministry of Religious Affairs of the Republic of Indonesia. This study provides an initial overview of the implementation of the Love-Based Curriculum in an Early Childhood Education institution under the supervision of the Ministry of Religious Affairs, an area that has rarely been reported in previous studies.